Multifunctional Dipoles Enabling Enhanced Ionic and Electronic Transport for High-Energy Batteries - Cao, Shihai; Sun, Yuntong; Li, Yinghao; Wang, Ao; Zhang, Wenyao; Hao, Zhendong; Lee, Jong‑Min (Nano-Micro Letters, 2026)
Achieving high-energy density remains a key objective for advanced energy storage systems. However, challenges, such as poor cathode conductivity, anode dendrite formation, polysulfide shuttling, and electrolyte degradation, continue to limit performance and stability. Molecular and ionic dipole interactions have emerged as an effective strategy to address these issues by regulating ionic transport, modulating solvation structures, optimizing interfacial chemistry, and enhancing charge transfer kinetics. These interactions also stabilize electrode interfaces, suppress side reactions, and mitigate anode corrosion, collectively improving the durability of high-energy batteries. A deeper understanding of these mechanisms is essential to guide the design of next-generation battery materials. Herein, this review summarizes the development, classification, and advantages of dipole interactions in high-energy batteries. The roles of dipoles, including facilitating ion transport, controlling solvation dynamics, stabilizing the electric double layer, optimizing solid electrolyte interphase and cathode–electrolyte interface layers, and inhibiting parasitic reactions—are comprehensively discussed. Finally, perspectives on future research directions are proposed to advance dipole-enabled strategies for high-performance energy storage. This review aims to provide insights into the rational design of dipole-interactive systems and promote the progress of electrochemical energy storage technologies. Highlights: 1 Offers a thorough review on the mechanism of molecular and ion dipoles in high-energy batteries, covering development, classification, and multifaceted roles in battery systems. 2 Elucidates how molecular and ion dipoles regulate ionic transport, optimize solvation structures, strengthen the electric double layer, and construct stable solid electrolyte interphase/cathode–electrolyte interface layers, all of which boost battery performance. 3 Demonstrates the wide-ranging applications of dipole interactions in various battery systems, such as suppressing dendrites in lithium–metal batteries and improving the cycling stability of lithium–sulfur batteries. 4 Proposes future research directions including AI-assisted materials design, in-depth mechanism exploration, multidisciplinary integration, database establishment, and promoting practical applications, aiming to drive the development of high-energy batteries.